Comparison of oocyte maturity rates in recombinant Human Chorionic Gonadotropin (HCG) and triptorelin acetate triggers: A prospective randomized study - S, Lakshmanan; M, Saravanan; P, Senthil (Clinical Journal of Obstetrics and Gynecology, 2020)
Luteinizing Hormone (LH) like exposure in the mid cycle for inducing the oocyte maturation is the very crucial step in the success of ICSI treatment. Introduction of LH surge endogenously by GnRH-agonist for ﬁnal oocyte maturation induction, may be more physiological compared with the administration of HCG. Since GnRH agonist would induce FSH surge also along with LH surge, as happens in natural cycle. However, the effects of giving HCG trigger for inducing only LH surge and giving GnRH agonist trigger for inducing both LH and FSH surge, in patients treated for ICSI with GnRH antagonists need more research. Sub fertile patients planned for ICSI, meeting the requirement of inclusion criteria, were started with recombinant FSH from day 2 of menstrual cycle. GnRH antagonists were started from day 6 of stimulation. FSH dose was adjusted according to the individual response. Trigger was planned when the lead follicle reaches 24 mm. For triggering, 100 patients were randomized to receive Recombinant HCG trigger and Triptorelin acetate trigger. Oocyte retrieval was done 36 hours after Recombinant hCG Trigger and 35 hours after Triptorelin acetate trigger. The oocyte maturity rate was assessed by the number of metaphase II oocytes retrieved.